2011
DOI: 10.1177/0032885511409869
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Sexuality in Women’s Prisons

Abstract: The literature on sexuality in women's correctional facilities has identified a variety of sexual behaviors in which female convicts and prison staff participate. However, no single taxonomy has been developed that adequately describes the range of sexual behaviors found within the confines of women's prisons. The ensuing analysis rectifies this deficiency by delineating a typology of the same. First, the classification system specifies the scope of sexual activities operating within female correctional enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Furthermore, as stated above, power and coercion are essential when examining sexual misconduct because inmates are unable to consent, based on their status (Asbridge, 2007; Buell & McCampbell, 2003; Coolman, 2003; De Amicis, 2005; GAO, 1999; Pardue et al, 2011). Yet, approximately three fourths of states do not mention power or disciplinary authority over inmates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, as stated above, power and coercion are essential when examining sexual misconduct because inmates are unable to consent, based on their status (Asbridge, 2007; Buell & McCampbell, 2003; Coolman, 2003; De Amicis, 2005; GAO, 1999; Pardue et al, 2011). Yet, approximately three fourths of states do not mention power or disciplinary authority over inmates.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the proximity of and access to inmates by correctional officers, as well as the isolation of correctional environments, romantic relationships and sexual involvement may occur (Baro, 1997). However, the concern is that the power disparity between correctional officers and inmates sets up situations in which officers may use the power of their position to intimidate and/or coerce inmates into sexual acts (Asbridge, 2007; Buell & McCampbell, 2003; Coolman, 2003; De Amicis, 2005; GAO, 1999; Pardue, Arrigo, & Murphy, 2011). Given this power imbalance, consensual sexual relationships between correctional staff and inmates are socially and legally prohibited.…”
Section: Sexual Misconduct In Correctional Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although extant studies have revealed much on the pairwise relationship between the outcome of interest and individual risk factors (e.g., between prior history and RH placement or between aggression and RH placement), there has been relatively scant attention on how these risk factors bundle with each other, and how they jointly shape the need for specifically focused interventions. It is common for actors in the criminal justice system to separate criminal-justice-involved individuals into different types and treat each perceived type accordingly (Clements, 1996; Pardue et al, 2011). Compared with the more common and conventional analyses relying on regression coefficients for individual risk factors, the type-based approach is gaining popularity in domains such as criminal careers (Nieuwbeerta et al, 2011) and courts and sentencing (Kimchi, 2019).…”
Section: Restrictive Housing: What We Knowmentioning
confidence: 99%
“…W kontekście omawianego zagadnienia warto przybliżyć pojęcie zaczerpnięte z amerykańskiej literatury, jailhouse turnout [19] (które można zdefiniować jako "homoseksualną prostytucję penitencjarną"), określające penitentów (zarówno kobiety, jak i mężczyzn) decydujących się na aktywność homoseksualną tylko podczas wyroku [18,20,21], często z hedonistycznych pobudek związanych z chęcią wejścia w posiadanie deficytowych dóbr i towarów. Dualistyczny (emocjonalny i materialny) charakter istniejących między więźniarkami relacji potwierdzają wypowiedzi respondentek przebywających w izraelskim zakładzie karnym dla kobiet Neve Tirza.…”
Section: Model Deprywacjiunclassified